A novel approach to a rare case of non-islet cell hypoglycaemia. (7th July 2021) - Dharmaputra, R K; Wan, K L; Samad, N; Herath, M; Wong, J; Sarlos, S; Holdsworth, S R; Naderpoor, N
Abstract : Summary: Insulin autoimmune syndrome (IAS) is a rare cause of non-islet cell hypoglycaemia. Treatment of this condition is complex and typically involves long-term use of glucocorticoids. Immunotherapy may provide an alternative in the management of this autoimmune condition through the suppression of antibodies production by B-lymphocyte depletion. We present a case of a 62-year-old male, with refractory hypoglycaemia initially presenting with hypoglycaemic seizure during an admission for acute psychosis. Biochemical testing revealed hypoglycaemia with an inappropriately elevated insulin and C-peptide level and no evidence of exogenous use of insulin or sulphonylurea. Polyethylene glycol precipitation demonstrated persistently elevated free insulin levels. This was accompanied by markedly elevated anti-insulin antibody (IA) titres. Imaging included CT with contrast, MRI, pancreatic endoscopic ultrasound and Ga 68-DOTATATE position emission tomography (DOTATATE PET) scan did not reveal islet cell aetiology for hyperinsulinaemia. Maintenance of euglycaemia was dependent on oral steroids and dextrose infusion. Complete resolution of hypoglycaemia and dependence on glucose and steroids was only achieved following treatment with plasma exchange and rituximab. Learning points: Insulin autoimmune syndrome (IAS) should be considered in patients with recurrent hyperinsulinaemic hypoglycaemia in whom exogenous insulin administration and islet cell pathologies have been excluded. Biochemical techniques play an essential role in establishing high insulin concentration, insulin antibody titres, and eliminating biochemical interference. High insulin antibody concentration can lead to inappropriately elevated serum insulin levels leading to hypoglycaemia. Plasma exchange and B-lymphocyte depletion with rituximab and immunosuppression with high dose glucocorticoids are effective in reducing serum insulin levels and hypoglycaemia in insulin autoimmune syndrome (IAS). Based on our observation, the reduction in serum insulin level may be a better indicator of treatment efficacy compared to anti-insulin antibody (IA) titre as it demonstrated greater correlation to the frequency of hypoglycaemia and to hypoglycaemia resolution.